Voter reactions to incumbent opportunism - Schleiter, P; Tavits, M (University of Chicago Press, 2018)
Opportunistic incumbent behavior to gain electoral advantage flies in the face of democratic accountability and should elicit voter disapproval. Yet incumbents routinely behave opportunistically. This observation is puzzling. We address this puzzle by offering the first systematic, individual-level analysis of voter reactions to opportunism. We combine four original surveys with embedded experiments and focus on a common form of opportunism in parliamentary systems—opportunistic election timing to favorable economic conditions. We find that opportunism negatively affects support for the incumbent because it engenders voter concern about the incumbent’s future performance and raises significant concerns about procedural fairness. However, under good economic performance, which often triggers electoral opportunism, voters are still more likely to support than oppose the incumbent despite their negative reaction to opportunism.